An Analysis of Teacher's Feedbacks on Students' Writings at SMAN 4 Padang - Elsya Dwi Wahyuni; Yetti Zainil; Witri Oktavia (Universitas Negeri Padang, 2019)
This research aimed to know the effect of giving feedback on student’s writing skill. This research is descriptive research. The population in this research is students of X MIA 6 and XI MIA 7. The sample was taken by using simple random sampling. There are at least 67 students that become the sample of the research. The data collected is in the form of writings before receiving pre-feedback and post-feedback. Each eleventh grade students was asked to write two giving suggestion dialogues meanwhile each tenth grade students were asked to write dialogue about advertisement and recount text. The students will be provided with feedback related to the mistakes in language structures after that the students were asked to revise their texts based on the feedback given to them. The feedbacks provided to the students are direct feedback and indirect feedback which is indirect feedback is divided into two that is coded and uncoded. From the research it is found that coded indirect feedback delivered significant effect in helping the students to improve their writing skills with proper language structure. Direct feedback, on the other hand, was helpful enough but it was not as good as coded indirect feedback. Evenmore, uncoded indirect feedback was not that influential to the students’ writings since they still committed mistakes after receiving the feedback.